Samuelsonian Economics and the Twenty-First Century 2006
DOI: 10.1093/acprof:oso/9780199298839.003.0016
|View full text |Cite
|
Sign up to set email alerts
|

Protection and Real Wages: The Stolper–Samuelson Theorem

Abstract: This chapter examines the Stolper–Samuelson's Theorem under varying conditions and assumptions. Using a previous reformulation of the theorem, it demonstrates that when the relative prices for labor-intensive goods fall, real wages decline in that sector, and the returns to other factors increase, resulting in a redistribution effect. The model had been robust in its predictions. When the number of goods and factors is increased, at least one factor is likely to gain or lose. The model is relevant for modern p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The prevailing scholarly literature concerning the possible determinants of attitudes toward trade traces its origins to the work of Stolper and Samuelson (1941), whose theory suggests that individuals' personal economic condition shapes their views on trade, with those in occupations that are more reliant on U.S. exports more likely to disfavor increased trade with other nations (see also Chipman, 1969;Deardorff and Stern, 1994;McCulloch, 2006). The reason for this originates in the uneven benefits known to result from economic specialization; arguably, certain economic factors, including human capital, suffer in a trade relationship.…”
Section: Economic Self-interestmentioning
confidence: 99%
“…The prevailing scholarly literature concerning the possible determinants of attitudes toward trade traces its origins to the work of Stolper and Samuelson (1941), whose theory suggests that individuals' personal economic condition shapes their views on trade, with those in occupations that are more reliant on U.S. exports more likely to disfavor increased trade with other nations (see also Chipman, 1969;Deardorff and Stern, 1994;McCulloch, 2006). The reason for this originates in the uneven benefits known to result from economic specialization; arguably, certain economic factors, including human capital, suffer in a trade relationship.…”
Section: Economic Self-interestmentioning
confidence: 99%
“…Among the modern theories about international commerce, one of the most important contributions has been the theorem developed by Wolfgang Stolper and Paul Samuelson in 1941, which is one of the main results of the Heckscher-Ohlin theory (Neary, 2004). The general equilibrium theory of commerce contributed by Eli Heckscher and Bertil Ohlin opened a new line of research "focused in the differences of the relative intensity of factors through industry and the differences in the relative abundance of factors through countries" (McCulloch, 2006) concluding that each country will export those products that are made by the abundant production factor and will import products where the production factor is scarce.…”
Section: Free Trade Theory and Its Influence At Wage Inequalitymentioning
confidence: 99%
“…Feenstra (2010) has shown that employment and relative wages for skilled workers vis à vis less-skilled workers have risen in both developed and developing countries; these results were consistent with Stolper-Samuelson predictions for developed countries, but not for developing ones. For a more favourable view see McCulloch (2006).…”
mentioning
confidence: 99%